Kinetic and Mechanism of Oxidation of Oxalic Acid by Cerium (IV) - Mohammed, Dr. Ammar J. (Al-Khwarizmi Engineering Journal, 2017)
Kinetic and mechanism studies of the oxidation of oxalic acid by Cerium sulphate have been carried out in acid medium sulphuric acid. The uv- vis. Spectrophotometric technique was used to follow up the reaction and the selected wavelength to be followed was 320 nm. The kinetic study showed that the order of reaction is first order in Ce(IV) and fractional in oxalic acid. The effect of using different concentration of sulphuric acid on the rate of the reaction has been studied a and it was found that the rate decreased with increasing the acid concentration. Classical organic tests was used to identify the product of the oxidation reaction, the product was just bubbles of CO2.